(untitled) (International relations and international law Journal, 2018)
This article analyzes the works of Western scholars, engaged in history, politics, economy and culture of Kazakhstan. We consider the point of view of different authors that focus not only on issues of geopolitics, security and international position of Kazakhstan, but also devoted to the internal problems of the state, political and socio-economic development. By the end of the 2000s the impression that foreign interest in the Central Asian region has exhausted itself, that everything has already been written. It seems that the West has lost the geopolitical interest in Central Asia, which is supported by the presence of US and NATO forces in Afghanistan. And all the changing dramatically: on the one hand, the West is scared Russia’s desire to speed up the creation of the Eurasian Union; on the other – strengthening of China in Central Asia is also not satisfied with the Western strategists. It also may include factors of Iran, India and Afghanistan, again, to understand that the geopolitical struggle over Central Asia does not disappear, but is entering a new phase. These findings come after analyzing the works of the authors underwritten Western researchers. Key words: Republic of Kazakhstan, Western researches, security issue, historiography, political and socio-economic development.